Street Names in Phitsanulok Municipality Area: a Linguistic Lanscape Study : ชื่อถนนในเขตเทศบาลนครพิษณุโลก: การศึกษาตามแนวภูมิทัศน์ภาษาศาสตร์ - Mahamontri, Wararat (Mekong-Salween Civilization Studies Journal, 2025)
The distinctiveness of street names in Phitsanulok Municipality area lies in the fact that they derived from the names of Thai kings and historical figures. However, data connecting the city to those personages are still lacking, and origins of the names of streets built in later periods are still incomplete. This research article aims to study the origins of street names in present-day Phitsanulok Municipality area and to analyze the symbolic meaning of the names using the Linguistic Landscape framework to reflect the concept involved in naming the streets located in public areas. The data comprising 58 street names were collected from street name signs, Phitsanulok Province website, Tourism Authority of Thailand in Phitsanulok, Google Maps of Phitsanulok, and various printed materials. The results reveal 7 sources of origin, namely, in order of frequency, names of the ruling class, names or words suggesting the people associated with the construction of the streets or those using the streets, place names, names related to Buddhism, names of animals, names of tools, and names of government projects. When analyzed using the Linguistic Landscape framework, the street names are found to reflect symbolic meanings relating to areas in Phitsanulok City in 7 historical, social and cultural aspects as follows: 1) The significance of historical figures related to the city; 2) The significance emphasized upon King Naresuan’s best soldiers 3) The importance of King Naresuan’s victory in the Elephant Duel; 4) The relations with Buddhism; 5) The honor bestowed upon citizens who donated their lands for the construction of public streets or the commemoration of citizens connected to the constructions of the streets or of important individuals who used the streets; 6) The sites of important buildings both in the past and at present; and 7) The public administration of land utilization. In addition, the street names are also related to their locations in the city plan of Phitsanulok Municipality. The names of kings, queens and crown princes are mostly found within the radius of one kilometer of the city center starting from Phitsanulok Train station and Clock Tower. This reflects the respect paid to the monarchy that played vital roles in Phitsanulok City. Street names adopted from names of nobilities are usually found to be further away from the city center. Lastly, street names derived from names of animals are found to be the furthest from the city center. The names of the streets in Phitsanulok Municipality area, therefore, have an important symbolic function of reflecting the concept of naming streets in relation to various aspects of Phitsanulok City and showcasing the identity of the city as a historical city though the use of language in public areas.